Instructional Materials and Quality in Public Primary Schools in Southwestern Nigeria - Chinedu I. Okeke; Timothy Olugbenga Ajadi (Indonesia Approach Education, 2023)
The study identified the instructional materials that are available and examined the level of its utilization in public primary schools in Southwestern Nigeria. In addition, it established the influence of instructional materials on instructional quality in public primary schools in Southwestern Nigeria. This study adopted descriptive design with a sample size of 450 respondents selected from the population of the study with the use of multi-stage sampling procedure. Instructional Materials Availability, Utilization and Instructional Quality Questionnaire (IMAUIQ) was used to collect data from the respondents which was trial tested on 90 respondents from selected public primary schools in local governments outside the selected ones for the study. The result revealed that chalkboard 450(100%) and textbooks 300(67%) are the predominant instructional materials available. Chalkboard 450(100%) was found to be sufficiently utilized. The result further showed that instructional materials have significantly influence on instructional quality in public primary schools in Nigeria. This is because the calculated value (4.82) is greater than the critical value (3.84) at 0.05 level of significance. The study concluded that there is inadequate utilization of instructional materials with their attendant consequences on instructional quality in public primary schools in Southwestern Nigeria.